2017
DOI: 10.1093/cvr/cvx164
|View full text |Cite|
|
Sign up to set email alerts
|

Obesity-induced vascular dysfunction and arterial stiffening requires endothelial cell arginase 1

Abstract: Vascular dysfunctions in diet-induced obesity are prevented by deletion of arginase 1 in vascular endothelial cells or arginase inhibition. These findings indicate that upregulation of arginase 1 expression/activity in vascular endothelial cells has an integral role in diet-induced cardiovascular dysfunction and metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
54
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 75 publications
5
54
2
1
Order By: Relevance
“…The major differences between healthy subjects and patients with T2DM in the current study, beyond indices of glucose, are BMI and waist/hip ratio. Previous studies have pointed out that arginase plays a central role in vascular dysfunction in obesity, which suggest that obesity could confound our results . However, El Assar et al .…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The major differences between healthy subjects and patients with T2DM in the current study, beyond indices of glucose, are BMI and waist/hip ratio. Previous studies have pointed out that arginase plays a central role in vascular dysfunction in obesity, which suggest that obesity could confound our results . However, El Assar et al .…”
Section: Discussionmentioning
confidence: 72%
“… have shown that high glucose induces up‐regulation of arginase 1 in bovine coronary endothelial cells via a mechanism involving NADPH oxidase‐derived ROS and up‐regulation of Rho kinase, which in turn reduces NO bioavailability. Moreover, it has been shown that ED induced by ex vivo exposure to high glucose/palmitate was completely reversed by acute administration of an arginase inhibitor . Collectively, these data suggest an intriguing interaction between glucose and arginase in T2DM in the regulation of endothelial function.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Diabetes is an independent risk factor for vascular complications (such as atherosclerosis of the coronary artery and stroke) and a main cause of the prevalence and mortality of cardiovascular diseases . Vascular dysfunction results from a chronic hyperglycaemic state, which leads to increased oxidative stress, vascular fibrosis and thickening, resulting in arteriosclerosis . In diabetic patients, arteriosclerosis is an important and dangerous complication.…”
Section: Introductionmentioning
confidence: 99%
“…Factors involved in the pathogenesis of diabetic retinopathy include inflammation, oxidative stress, and reduced endothelial nitric oxide (NO) production [3][4][5][6]. Studies have indicated that obesity and diabetes substantially affect the retina and its interactive vascular, neuronal, glial, and immune cells [5,7].We, and others, previously reported the crucial role of arginase in the development of diabetes-induced pathologies and dysfunctions [3,[8][9][10]. Arginase, a key enzyme in the urea cycle, can reciprocally regulate NO production by competing with nitric oxide synthase (NOS) for their shared substrate, L-arginine [11,12].…”
mentioning
confidence: 99%